Frequency of Maternal Morbidity in High Order Cesarean Section - Gandapur, Shallozan Khannum; Ali, Sadia; Khan, Sabba (Indus Journal of Bioscience Research, 2025)
Background: High-order cesareans are linked with higher maternal morbidity, including dense adhesions, placenta previa, rupture of uterus, and injury to the bladder. All these complications are frequently attributed to multiple procedures with resultant scarring and alteration of placental attachment. It is important to identify potential causes for these morbidities, including age, BMI, socioeconomic status, and residential area, as these are important to enhance better patient outcomes. Objective: To determine the frequency of maternal morbidity in high order cesarean section at Hayatabad Medical complex Peshawar. Study Design: Descriptive, cross-sectional study. Duration and Place of Study: The study was conducted between July 2024 and January 2025 at the Department of Obstetrics and Gynecology, Hayatabad Medical complex Peshawar. Methodology: The study recruited a total of 150 pregnant women aged 18–40 years with singleton pregnancy and undergoing elective high-order cesarean section. Information on demographic (age, gestational age, parity, BMI, socioeconomics, and residence), maternal morbidities, and maternal health outcomes was recorded. Maternal morbidities were identified and graded with respect to operative findings noted in cesarean section. Results: The study found a high prevalence of maternal morbidities: dense adhesions (56%), placenta previa (87.3%), uterine rupture (83.3%), and bladder injury (88.7%). Stratified analysis revealed that younger women (age ≤30 years) had a significantly lower incidence of dense adhesions, while women with higher BMI and lower socioeconomic status had higher occurrences of placenta previa and uterine rupture. Conclusion: High-order cesarean sections are associated with an increased risk of maternal morbidities, particularly in women with higher BMI, lower socioeconomic status, and rural residence.